2018
DOI: 10.3324/haematol.2017.181842
|View full text |Cite
|
Sign up to set email alerts
|

Association of mutations with morphological dysplasia in de novo acute myeloid leukemia without 2016 WHO Classification-defined cytogenetic abnormalities

Abstract: Despite improvements in our understanding of the molecular basis of acute myeloid leukemia (AML), the association between genetic mutations with morphological dysplasia remains unclear. In this study, we evaluated and scored dysplasia in bone marrow (BM) specimens from 168 patients with de novo AML; none of these patients had cytogenetic abnormalities according to the 2016 World Health Organization Classification. We then performed targeted sequencing of diagnostic BM aspirates for recurrent mutations associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…11,12 These AML subtypes are themselves nonspecific because of variation in the understanding of their pathogenetic links, especially in cases without overt dysplasia. 13,14 Without dysplasia, reliance is mainly on anamnestic clinical information that might be unavailable or cannot be correctly assigned because of a short prodromal history of antecedent myeloid neoplasm. Additionally, supervised analytic strategies to reproduce current pathomorphologic entities as gold standard using molecular features have been modest.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These AML subtypes are themselves nonspecific because of variation in the understanding of their pathogenetic links, especially in cases without overt dysplasia. 13,14 Without dysplasia, reliance is mainly on anamnestic clinical information that might be unavailable or cannot be correctly assigned because of a short prodromal history of antecedent myeloid neoplasm. Additionally, supervised analytic strategies to reproduce current pathomorphologic entities as gold standard using molecular features have been modest.…”
Section: Introductionmentioning
confidence: 99%
“…BM aspirate smears were evaluated for blast count as well as dysplasia in the erythroid, granulocytic, and megakaryocytic lineages as previously reported. 22 Dysplasia was scored in a blinded fashion by 3 board-certified, expert hematopathologists (O.P., R.P.H., and O.K.W.). Each lineage was assessed for individual dysplastic features (erythroid precursors: megaloblastic change, multinucleation, and nuclear irregularities; granulocytic precursors: abnormal nuclear shape and hypogranulation; megakaryocytes: micromegakaryocytes, widely separated nuclear lobes, and hypolobated nuclei).…”
Section: Bm Morphologic Evaluationmentioning
confidence: 99%
“…The severity of dysplasia in each lineage was scored on a scale of 0 to 4 (0, no dysplasia; 1, mild dysplasia; 2, moderate dysplasia; 3, significant dysplasia; 4, severe dysplasia), and the percentage of dysplastic cells in each lineage was quantified, as previously described. 22…”
Section: Bm Morphologic Evaluationmentioning
confidence: 99%
“…Previous studies showed that mutations in CEBPA, NPM1, FLT3-ITD, NRAS, ASXL1, EZH2, BCOR, or STAG2 were altered in AML-MRC, particularly with the presence of dysplasia and a history of MDS and/or MDS-related cytogenetic abnormalities. 3,7,[34][35][36] These mutations might also affect the relapse incidences after HCT. Second, the types of induction chemotherapy and consolidation or salvage chemotherapy following induction chemotherapy could not be evaluated due to insufficient data.…”
Section: Discussionmentioning
confidence: 99%